A curva catenária como aplicação da função exponencial - Mendes, Marlon Freitas (Universidade Federal de São Carlos, 2017)
The current study aims to elaborate a didactic sequence to study the catenary curve through the dynamic geometry perspective. In onder to highlight the importance of using software/application to better understand the function and its graphical representation, a study has been made on its historical development, notation, construction as well as its properties. Therefore, a lesson plan on the curve will be applied to High School students. Based on their reports, we intend to analyze and discuss these results.
Keywords: Catenária; Exponencial; Cosseno hiperbólico; Geogebra; Catenary; Exponential; Hyperbolic cossene; Geogebra; CIENCIAS EXATAS E DA TERRA